Chlorophyll-aConcentration in Waters in the Riau University area, Pekanbaru, Riau Province - Lubis, Helfrida; H. Simarmata, Asmika; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT In the Riau University area there are several shallow waters. Activities conducted around the waters may contribute the input of organic and inorganic pollutant into the waters. The pollutant may increase the fertility of the water and it is reflected in the concentration of chlorophyll-a content in the water. A research aims to determine the aquatic productivity based on chlorophyll-a concentration, has been carried out in March-April 2018. Sampling was carried out in three stations, namely stations 1 (around the LPPM building), station 2 (in the front of the Rectorate building), and station 3 (in the Fisheries Faculty reservoir). Water quality parameters measured were temperature, pH, transparency, DO, CO2, nitrate and phosphateconcentration. Samplings were conducted three times, once/week. Results shown that the chlorophyll-a concentration ranged from 4.04-5.12µg/L, temperature 30-310C, transparency 34-84 cm, depth 116-209 cm, DO 4.96-5.64 mg/L, CO2 14.64-17.31 mg/L, Nitrate 0.05-0.06 mg/L, phosphate 0.07-0.19 mg/L, and pH 6. Based on the chlorophyll-a concentration, the water of the waters in the Riau University area can be categorized as mesotrophic. Keywords: mesotrophic, water quality,reservoir FPK, organic matter, aquatic productivity